Pollution Characteristics and Key Reactive Species of Volatile Organic Compounds in Beijing-Tianjin-Hebei Area, China - Yanan Guan; Yihao Zhang; Yisen Zhang; Xiaoli Wang; Jing Han; Wenbo Song; Li’an Hou; Erhong Duan (Aerosol and Air Quality Research)
Abstract Volatile organic compounds (VOCs) are important precursors in the formation of ground-level ozone. In this study, the hourly mixing ratios of 61 ambient VOC species were monitored from 2018 till 2019 in 10 cities in the Beijing-Tianjin-Hebei (BTH) area of China, and the VOC distributions, speciation and photochemistry were also examined. The highest mixing ratios were found in the south, viz., Langfang (LF), Baoding (BD), Handan (HD) and Shijiazhuang (SJZ), and the lowest ones, in the north, viz., Chengde (CD) and Zhangjiakou (ZJK). In all of the cities, alkanes were the most abundant VOC component (50%), whereas ethane and propane were the most concentrated species. The mixing ratios of the VOCs exhibited a daily double peak as a result of the varying intensity of the photochemical reactions and the formation of the inversion layer. Additionally, the chemical reactivity of the VOCs was evaluated by calculating the loss rate of OH (LOH) for each species. Our results indicated that the alkenes and aromatics possessed higher LOH values as well as higher ozone formation potential (OFP) and secondary organic aerosol formation potential (SOAp) values than the alkanes. Based on the diagnostic ratios of propane/n-butane, propane/i-butane, cis-2-butane/trans-2-butane, toluene/benzene and xylene/ethylbenzene, motor vehicle emissions contributed significantly to the ambient VOCs in the area.